2007
DOI: 10.1189/jlb.0507296
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective activities of CD4+CD25+ regulatory T cells in an animal model of Parkinson’s disease

Abstract: Progressive loss of dopaminergic neurons in the substantia nigra pars compacta and their terminal connections in the striatum are central features in Parkinson's disease (PD). Emerging evidence supports the notion that microglia neuroinflammatory responses speed neurodegenerative events. We demonstrated previously that this can be slowed by adoptive transfer of T cells from Copolymer-1-immunized mice administered to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) recipients. The cellular basis for this neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
316
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(349 citation statements)
references
References 85 publications
13
316
1
4
Order By: Relevance
“…For this purpose, mice were treated with an acute toxicity regimen of MPTP, and after 7 d, histological analysis of DAergic neuron integrity and neurodegeneration in the SN were performed in midbrain sections by TH immunostaining and FJ-C labeling, respectively. Consistent with previous reports (6,7,10), results show that MPTP treatment of WT mice results in significant loss of DAergic neurons ( 40%) in the SNpc. Strikingly, D3R deficiency completely abolished MPTP-induced loss of DAergic neurons (Fig.…”
Section: D3r Deficiency Protects From Neurodegeneration Of Daergic Nesupporting
confidence: 82%
See 2 more Smart Citations
“…For this purpose, mice were treated with an acute toxicity regimen of MPTP, and after 7 d, histological analysis of DAergic neuron integrity and neurodegeneration in the SN were performed in midbrain sections by TH immunostaining and FJ-C labeling, respectively. Consistent with previous reports (6,7,10), results show that MPTP treatment of WT mice results in significant loss of DAergic neurons ( 40%) in the SNpc. Strikingly, D3R deficiency completely abolished MPTP-induced loss of DAergic neurons (Fig.…”
Section: D3r Deficiency Protects From Neurodegeneration Of Daergic Nesupporting
confidence: 82%
“…These studies have shown that nitrated a-synuclein is presented in cervical lymph nodes, which drain Ags from CNS, and elicits an Ag-specific CD4 + T cell response mediated by cells with the inflammatory phenotypes Th1 and Th17, which exacerbate the microglial activation and neuronal damage (5,8). In contrast, it has been demonstrated that CD4 + regulatory T cells (Tregs), which suppress function of inflammatory Th1 and Th17 cells, may also participate during PD, attenuating the destruction of DAergic neurons in the SN (7,10). Thus, this evidence supports the participation of a CD4 + T cell response during PD, which seems to be fundamental for the degeneration of DAergic neurons in the SN.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…This neuroprotective effect was later found to be mediated by the CD4 + type of T cells, suggesting the possible involvement of Treg cells (Laurie et al, 2007). Later work by the same group confirmed this hypothesis by showing that passive transfer to MPTP mice of activated Treg cells, but not effector T cells, efficiently suppressed microglial activation and afforded neuroprotection (Reynolds et al, 2007), suggesting that the immunomodulating abilities of Treg cells could potentially be utilized as a therapeutic approach against PD (Stone et al, 2009). …”
Section: Prospects For Syn-based Immunotherapy In Pdsupporting
confidence: 52%
“…While active immunization stimulates the immune system to produce antibodies against target proteins, passive immunization consists in directly administering antibodies that confer temporary protection against the disease. A third type of immunotherapy involving the activation of regulatory T-cells has also been explored for the potential treatment of AD and PD [59,60]. The advantage of humoral immunotherapy over other approaches is that it allows for the generation of antibodies targeting specific conformations of Aβ, tau, or α-syn (monomers, oligomers, and/or fibrils) (Fig.…”
Section: Introductionmentioning
confidence: 99%